Twisted 3 planet of the twisted - Zafra, Jessica (Pasig City Anvil Publishing, Inc., 1998)
Generation X icon Zafra continues her quest for world domination as she rants, complains, reminisces, and comments on anything and everything under the sun with her usual acerbic humor.
Spine title: Twisted 3: planet of the twisted.
Keywords: Philippine essays (English); Literary journeys